2020
DOI: 10.3390/molecules25225426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin B Complex Treatment on Macrophages to Schwann Cells Association during Neuroinflammation after Peripheral Nerve Injury

Abstract: Peripheral nerve injury (PNI) triggers a complex multi-cellular response involving the injured neurons, Schwann cells (SCs), and immune cells, often resulting in poor functional recovery. The aim of this study was to investigate the effects of the treatment with vitamin B (B1, B2, B3, B5, B6, and B12) complex on the interaction between macrophages and SCs during the recovery period after PNI. Transection of the motor branch of the femoral nerve followed by reconstruction by termino-terminal anastomosis was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
(72 reference statements)
2
9
0
Order By: Relevance
“…On the contrary, our findings displayed that VBC treatment contributed to the increased nerve nuclear density at the end of the disease. These observations could be correlated with our recently published results showing that VBC caused a time-dependent rise of cell number ( i.e., macrophages/Schwann cells) and their mutual interactions that are most likely associated with the regeneration of the injured nerve [ 26 , 27 ]. In addition to Schwann cells, one study outlined the significance of the olfactory nerve glia, which is more efficient in removing myelin debris and promoting neuronal regeneration than Schwann cells.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the contrary, our findings displayed that VBC treatment contributed to the increased nerve nuclear density at the end of the disease. These observations could be correlated with our recently published results showing that VBC caused a time-dependent rise of cell number ( i.e., macrophages/Schwann cells) and their mutual interactions that are most likely associated with the regeneration of the injured nerve [ 26 , 27 ]. In addition to Schwann cells, one study outlined the significance of the olfactory nerve glia, which is more efficient in removing myelin debris and promoting neuronal regeneration than Schwann cells.…”
Section: Discussionsupporting
confidence: 86%
“…In our previously published paper [ 25 ], we have shown that VBC (a complex of vitamins B1, B2, B3, B5, B6, and B12) treatment enhanced the motor nerve regeneration and the recovery of muscle function in a rat model of peripheral nerve injury. Briefly, VBC therapy improved axonal regeneration, as well as functional recovery, by reducing both Schwann cell decline and deterioration of myelin sheath [ 26 ]. Moreover, we have demonstrated that treatment with VBC complex accelerated this recovery via attenuation of neuroinflammation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ehmedah et al demonstrated a modulatory effect on the macrophage-SC interaction during the early stages of Wallerian degeneration after nerve injury. Treatment with the B vitamin complex accelerated the transition from the non-myelin to myelin-forming SCs, which was accompanied by an increase in macrophage-SC interactions toward accelerating the transition from indispensable inflammation to nerve repair processes after peripheral nerve injury [130]. In the following, we report available knowledge on the different members of the vitamin B complex, always mainly focusing on peripheral nervous system studies.…”
Section: Water-soluble Vitamins Vitamin Bmentioning
confidence: 99%
“…In mice with methionine-high and B6, folate, and B12-low diets, microhemorrhages and amyloid-plaque buildup was observed in neural tissue, corresponding with increased inflammatory cytokine expression, emphasizing the protective effect of methyl donors and the dangerous impact of homocysteine [ 138 , 139 ]. B complex supplementation was shown to have a beneficial effect on peripheral nerve repair; B vitamin injections reduced inflammatory cytokine expression, polarized macrophages towards an M2 phenotype, and induced an anti-inflammatory phenotype in Schwann cells following injury [ 140 ]. The fact that B12 is implicated in neuroprotection in both the central and peripheral aspects of the nervous system suggests that neural tissue has a particular dependence on vitamin B12 that is still being elucidated, with a specific interest in a putative role for injury prevention and repair.…”
Section: Folate B12 and Sam: Links To Tissue-specific Inflammationmentioning
confidence: 99%